Burkina Faso : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2005)
This Selected Issues and Statistical Appendix paper on Burkina Faso reviews background information and analytical support for key policy issues. This paper extends the results from the debt sustainability analysis for Burkina Faso and develops two alternative debt ratios that are suitable for assessing the impact of discount rate changes on the debt burden of the country. To better understand the implications of discount rate changes on the debt situation, the set of available debt ratios by developing two new measures of debt burden were extended.